STUDENTS’ PRONUNCIATION ANALYSIS OF ENGLISH INFLECTIONAL –S ENDING AT SMA PANGUDI LUHUR - Eka Agustina; Mega Utami; Nanda Aprilia; Epita Sari; Ramadhoni Ramadhoni (Universitas Wiralodra, 2024)
This study focused on the most dominant way of Students' Pronunciation of the English Inflectional “-S” Ending at the Tenth Grade of SMA Pangudi Luhur. The writer used the quantitative content analysis method to know the dominant way students pronounce the Inflectional “-S” Ending that was produced by 43 respondents. The technique of collecting the data was an instrument test consisting of 30 words of inflectional “-S” endings of two paragraphs and observation. Techniques for analyzing the data are coding category, coding material, data display, and analyzing and interpreting the result. Moreover, from the Pronunciation of inflectional “-S” endings, there were three possible inflectional “-S” endings such as /s/, /z/, and/iz/. Based on the findings, the dominant error in students' Pronunciation of inflectional test was uninflected with /iz/ endings 1.131 (37%) words, /z/ endings 1.129 (33%) words, and /s/ 1.057 (30%) words. The most uninflected words made by the students were/iz/ and the “-S” in the third person singular present tense.